RENT SEEKING PRACTICE : A NEW CORRUPTION CULTURE WITHIN INDONESIAN POLITICION AND BIROCRATION - Widanarto, Widanarto (Jurnal Politikom Indonesiana, 2017)
Abstract The practice of rent seeking is a new cultural phenomenon of corruption in Indonesia since implementation of government reform and regional autonomy. The culture is the case among the corruption of public officials and politicians collaborated with entepreuneurs and people who interested in the effort to get around the cracks of public policy for the benefit of serving and enriching themselves. The practice of rent seeking can take place in various activities of government and politics from the sale of official promotion and recruitment, the budget of allocation for programme activities and government projects, political compromise in the formulation and determination of public policy, political compromise ahead of the elections or regional elections and many more. The practice of rent seeking can not be eliminated as long as the state does not implement a democratic political system, upholding the rule of law or law enforcement, welfare oriented development and social justice, and that is no less important is a decisive leadership, visionary, honest, and legitimate without any political engineering. Keywords : Rent Seeking, Corruption, Democracy and Rule of Law